2017
DOI: 10.1371/journal.pone.0173420
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia in kidney transplanted women; Outcomes and a simple prognostic risk score system

Abstract: Women pregnant following kidney transplantation are at high risk of preeclampsia. Identifying the effects of preeclampsia on pregnancy outcome and allograft function in kidney transplanted women, and predicting which women will require more targeted follow-up and possible therapeutic intervention, could improve both maternal and neonatal outcome. In this retrospective cohort study of all pregnancies following kidney transplantation in Norway between 1969 and 2013, we used medical records to identify clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 22 publications
0
21
0
5
Order By: Relevance
“…While prior studies have not reported higher rates of neonatal mortality and stillbirths in kidney transplant recipients, the current study finding is highly significant. Possible reasons could be prematurity, preeclampsia or presence of other risk factors like hypertension, proteinuria, and serum creatinine of 1.5 mg/dl or higher [2628]. While it was not possible to determine the exact cause for stillbirth or neonatal mortality, this study finding is critical for counselling of women of child bearing age contemplating pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…While prior studies have not reported higher rates of neonatal mortality and stillbirths in kidney transplant recipients, the current study finding is highly significant. Possible reasons could be prematurity, preeclampsia or presence of other risk factors like hypertension, proteinuria, and serum creatinine of 1.5 mg/dl or higher [2628]. While it was not possible to determine the exact cause for stillbirth or neonatal mortality, this study finding is critical for counselling of women of child bearing age contemplating pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…However, for the second pregnancy, pre-eclampsia in a previous pregnancy was recognised to be a strong predictor of likely recurrence in transplanted women. 20 In conclusion, SPKT with stable pre-pregnancy graft function enabled this patient to achieve successful pregnancy. The risks of SPKT pregnancies appear similar to those in KT recipients; graft stability remains essential to minimizing these risks.…”
Section: Discussionmentioning
confidence: 77%
“…In our patient, the development of new hypertension and kidney graft dysfunction suggested super-imposed pre-eclampsia, prompting delivery in both pregnancies. Our patient had a preconception serum creatinine (<110 umol/L) that placed her at lower risk for adverse pregnancy outcome according to studies where serum creatinine was used to risk-stratify transplant pregnancies, [17][18][19][20] and also did not have chronic hypertension. However, for the second pregnancy, pre-eclampsia in a previous pregnancy was recognised to be a strong predictor of likely recurrence in transplanted women.…”
Section: Discussionmentioning
confidence: 99%
“…PE is the main reason for infant death, fetal body dysplasia, and damage of different maternal organs. [16][17][18] In a general sense, the development of PE is associated with pregnancy-induced hypertension and renal failure. 19 Therefore, it is important to clarify the specific molecular mechanism underlying the occurrence of PE and identify the molecules that regulate the development of PE.…”
Section: Discussionmentioning
confidence: 99%